Food aid for market development in Sub-Saharan Africa - Abdulai, Awudu; Barrett, Christopher B.; Hazell, Peter B. R. (International Food Policy Research Institute, 2004)
Food aid remains significant for food availability in many low-income countries in sub-Saharan Africa, helping to reduce the gap between food consumption needs and supply from domestic production and inventories and commercial imports. Food aid remains a contentious subject, however, and there have been many recent pleas for more effective use of the resource. This study explores how food aid might be used for domestic food market development to facilitate poverty alleviation and economic growth. There are obvious risks to using food aid for market development, just as there have been in using food aid to try to stimulate agricultural development. Because food aid necessarily expands local food supply, it needs to be well targeted if adverse producer price effects are to be avoided. In particular, if food aid can be targeted so as to relieve short-term working capital and transport capacity constraints to the development of downstream processing and distribution capacity in recipient country food marketing channels, for example by helping build farmer cooperative groups, then food aid could have salutary effects on sub-Saharan African agriculture." --Authors' Abstract